Weyl Fermions in VI3 Monolayer - Jia, Taoyuan; Meng, Weizhen; Zhang, Haopeng; Liu, Chunhai; Dai, Xuefang; Zhang, Xiaoming; Liu, Guodong (Frontiers in Chemistry, 2020)
We report the presence of a Weyl fermion in VI3 monolayer. The material shows a sandwich-like hexagonal structure and stable phonon spectrum. It has a half-metal band structure, where only the bands in one spin channel cross the Fermi level. There are three pairs of Weyl points slightly below the Fermi level in spin-up channel. The Weyl points show a clean band structure and are characterized by clear Fermi arcs edge state. The effects of spin-orbit coupling, electron correlation, and lattice strain on the electronic band structure were investigated. We find that the half-metallicity and Weyl points are robust against these perturbations. Our work suggests VI3 monolayer is an excellent Weyl half-metal.